The nature, extent and impact of multiple land uses on the agricultural landscape in Stellenbosch as manifestation of a post-productivist mode of agricultural change - Cloete, Gert Johannes Abraham (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.